Mastitis in Sheep - Procalcitonin Level as a Biomarker for Early Diagnosis - Akkuş, Tuğra; Yaprakci, Ömer; Mogulkoç, Mahmut Niyazi; Ekici, Mehmet; Demirtas , Ali Coşkun; Ates, Hüseyin (Acta Scientiae Veterinariae, 2024)
Background: Mastitis in sheep is significant due to its ability to cause both clinical and subclinical infections, being one of the most important diseases affecting dairy sheep worldwide. Infection caused by Staphylococcus aureus (S. aureus) is significant due to its ability to cause both clinical and subclinical mastitis. Procalcitonin (PCT) is a prohormone that increases in cases of bacterial inflammation, sepsis, and multiple organ failure. This study was conducted to determine changes in procalcitonin levels in subclinical and clinical mastitis in sheep. Materials, Methods & Results: The study used 60 Ivesi breed sheep that were within the 1st 45 days of lactation and had not received any medication in the past 20 days. The sheep were divided into 3 groups based on clinical examination, somatic cell count (SCC), California mastitis test (CMT), and results from bacteriological isolation and identification. Group 1 (n = 20) consisted of healthy sheep; Group 2 (n = 20) consisted of sheep with subclinical mastitis, and Group 3 (n = 20) consisted of sheep with clinical mastitis. Blood samples were collected from the jugular vein and then centrifuged. Serum Amyloid A (SAA), Haptoglobin (Hp), and Procalcitonin (PCT) levels were assessed using commercial kits. The obtained data were analyzed using one-way ANOVA. Body temperature and leukocyte count were found to be higher in the clinical mastitis group compared to the other groups (P < 0.001). Somatic cell count (SCC), SAA, Hp, and PCT levels were lowest in the healthy group and highest in the clinical mastitis group (P < 0.001). Significant positive correlations were found between procalcitonin and body temperature, leukocyte count, SCC, SAA, and Hp (r = 0.897, P < 0.01; r = 0.940, P < 0.01; r = 0.985, P < 0.01; r = 0.928, P < 0.01; r = 0.956, P < 0.01, respectively). Discussion: In our study, higher PCT levels were detected in sheep with clinical mastitis. This finding supports the theory that PCT increases in bacterial infections. The presence of infection triggers an inflammatory response, which increases procalcitonin (PCT) production. The increase in leukocyte count and PCT levels reflects the severity of the infection and the immune system's response. This parallel increase explains the positive correlation between PCT and leukocyte count observed in our study. Somatic cell count (SCC) is particularly indicative of mammary gland infections. During mastitis, somatic cells, especially leukocytes, increase in milk. This increase leads to elevated procalcitonin (PCT) levels as part of the inflammatory response. The high correlation between SCC and PCT indicates that both parameters increase in response to the presence and severity of infection. This parallel increase explains the positive correlation between SCC and PCT observed in our study. Serum amyloid A (SAA) is another indicator of the inflammatory response and is classified as an acute phase protein. Both SAA and PCT reflect the severity and extent of the inflammatory response. This parallel increase explains the positive correlation between SAA and PCT observed in our study. Haptoglobin (Hp) is another acute phase protein produced by the liver as part of the inflammatory response. Hp levels increase during infection or tissue damage. Similarly, procalcitonin (PCT) levels also rise in response to inflammatory cytokines. In our study, the positive correlation between Hp and PCT indicates that both biomarkers increase in response to the severity of inflammatory processes. In conclusion, procalcitonin may be a novel biomarker for diagnosing both subclinical and clinical mastitis in sheep. Keywords: sheep, haptoglobin, procalcitonin, biomarker, diagnosis, clinical mastitis, subclinical mastitis, bacterial infection.